Quality and flexible learning in Higher Education - Duart, Josep M. (Rastros Rostros, 2026)
Higher education is currently undergoing profound transformations as a result of increasing digitalization, internationalization, and student diversity. The traditionally accepted notions of quality and flexibility in education must now be understood as interdependent dimensions that guide the development of relevant and meaningful education. This chapter examines contemporary approaches to educational quality (continuous improvement, self-regulation, and a culture of quality) and argues for the value of a competency-based approach in the current context. It also delves into the dimensions of flexibility and its relationship to quality assurance. Based on a narrative analysis supported by recent documentary evidence, it presents examples of institutional success, such as those of the Open University of Catalonia (UOC), the Monterrey Institute of Technology and Higher Education (ITESM), the Open University of the United Kingdom, and a brief case study of the Cooperative University of Colombia (UCC). The role of emerging technologies (learning analytics and artificial intelligence) is discussed, and trends toward 2030 are projected.
Keywords: educational quality; flexibility; higher education; competencies; microcredentials; lifelong learning; learning analytics; artificial intelligence